Puberty is associated with increased deterioration of renal function in patients with CKD: data from the ItalKid Project. Issue 10 (25th July 2012) - Ardissino, Gianluigi; Testa, Sara; Daccò, Valeria; Paglialonga, Fabio; Viganò, Sara; Felice-Civitillo, Cristina; Battaglino, Francesco; Bettinelli, Alberto; Bordugo, Andrea; Cecchetti, Valeria; De Pascale, Salvatore; La Manna, Angela; et al.
Abstract : Objective: To analyse the timing of end stage renal disease in children with chronic kidney disease (CKD). Design: A population-based cohort study. Setting: A nationwide registry (ItalKid Project) collecting information on all patients with CKD aged <20 years. Patients: 935 children with CKD secondary to renal hypodysplasia with or without urologic malformation. In a subgroup of patients (n=40) detailed pubertal staging was analysed in relation to CKD progression. Main outcome measures: Kidney survival (KS) was estimated using renal replacement therapy (RRT) as the end-point. Puberty was staged by identifying the pubertal growth spurt. Results: A non-linear decline in the probability of KS was observed, with a steep decrease during puberty: the probability of RRT was estimated to be 9.4% and 51.8% during the first and second decades of life, respectively. A break-point in the KS curve was identified at 11.6 and 10.9 years of age in male and female patients, respectively. Conclusions: The present analysis suggests that puberty is associated with increased deterioration of renal function in CKD. The mechanism(s) underlying this unique and specific (to children) pattern of progression have not yet been identified, but it may be that sex hormones play a role in this puberty-related progression of CKD.